Design and Development of UI/UX for Viclerent Mobile Application in Online Vehicle Rental Services - Erwin Teguh Arujisaputra; Sunja Hana Salsabila; Sheira Putri Nabilla; Genta Nazwar Tarempa (Journal of Applied Information System and Informatic (JAISI), 2026)
— The advancement of digital technology has encouraged the emergence of mobile-based innovations, including vehicle rental services. However, many existing applications still fail to prioritize user convenience, resulting in unintuitive interfaces, unclear information, and inefficient navigation flows. This study aims to design and develop the user interface (UI) and user experience (UX) of the Viclerent mobile application, an online vehicle rental platform that emphasizes usability, accessibility, and user comfort. The design process adopts the Design Thinking approach, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. Data collection was conducted through questionnaires distributed to potential users to identify their needs, problems, and preferences in using digital vehicle rental services. The findings were analyzed to produce design artifacts such as User Personas, Empathy Maps, Affinity Diagrams, pain points, and solution ideas. These artifacts guided the creation of Wireframes and Prototypes using design tools, ensuring that the application design was structured, intuitive, and responsive. The Prototype was then tested with users to evaluate usability, satisfaction, and effectiveness in supporting the rental process. Results indicate that the proposed design improves transparency of rental costs, simplifies booking procedures, and enhances trust through features such as real-time vehicle availability, flexible payment methods, and reliable review systems. Overall, the Viclerent UI/UX design demonstrates the potential to deliver a user-friendly, efficient, and innovative digital solution, thereby improving accessibility, convenience, and satisfaction in mobile-based vehicle rental services.